1997
DOI: 10.1002/(sici)1098-237x(199705)81:3<355::aid-sce6>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Research traditions in comparative context: A philosophical challenge to radical constructivism

Abstract: Constructivism in science education has incorporated a multitude of perspectives. Many of these perspectives agree with the general assertion that knowledge is constructed. Two such projects are conceptual change theory and radical constructivism. In this article, I distinguish these two traditions based on four issues: ontology; epistemological commitments; view of learners; and authority of received ideas. I bring a philosophy of science perspective to bear, treating conceptual change theory and radical cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 36 publications
0
6
0
3
Order By: Relevance
“…Constructivism appears to require a relativist ontology; however, some constructivists seem to assume an ontologically neutral stance, not dissimilar to that of positivism (Von Glasersfeld, 1989a). Similar criticisms have been levelled at constructivists' epistemological views, Kelly (1997), for example, argues that constructivism "straddles an epistemological divide from a Cartesian metaphysics to a social view of knowledge transmission" (p. 356) (see, also, Bickhard, 1997). The origins of this confusion lie in the lumping together of the different forms of constructivism and these versions hold significantly different epistemologies (Good, Wandersee & St Julien, 1993;Matthews, 1992).…”
Section: Theoretical Concerns With Constructivismmentioning
confidence: 99%
See 2 more Smart Citations
“…Constructivism appears to require a relativist ontology; however, some constructivists seem to assume an ontologically neutral stance, not dissimilar to that of positivism (Von Glasersfeld, 1989a). Similar criticisms have been levelled at constructivists' epistemological views, Kelly (1997), for example, argues that constructivism "straddles an epistemological divide from a Cartesian metaphysics to a social view of knowledge transmission" (p. 356) (see, also, Bickhard, 1997). The origins of this confusion lie in the lumping together of the different forms of constructivism and these versions hold significantly different epistemologies (Good, Wandersee & St Julien, 1993;Matthews, 1992).…”
Section: Theoretical Concerns With Constructivismmentioning
confidence: 99%
“…Although some constructivist authors criticize positivism on the basis that since science is a social construction, it incorporates bias and ideologies, such a stance is not necessarily inconsistent with positivism. As Kelly (1997) sees it, "because scientific knowledge is factual…, biases represent a problem with scientific methods (something to watch out for), but not scientific knowledge" (p. 360). In other words, ideologies are inevitable in human inquiry, but this is insufficient to claim that there is not an independent reality.…”
Section: Theoretical Concerns With Constructivismmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology has previously been applied to interpret research in science education (Blanco & Nias, 1997, 1998Kelly, 1997;Chin & Brewer, 1993;Girbert & Swift, 1985;Linn & Songer, 1991;Niaz, 1993Niaz, , 1994Niaz, , 1995. According to Lakatos (1970), a research program consists of methodological rules: some tell us what paths of research to avoid (negative heuristic) and others tell us what paths to pursue (positive heuristic).…”
Section: Lakatosian Methodologymentioning
confidence: 99%
“…Nevertheless, sociological and anthropological studies of scientific knowledge and practices have demonstrated that connections between what a scientific community counts as a valid experiment and its relevance to what comes to be taken as (i.e., interactionally acknowledged as) scientific knowledge are established socially through conventionalized discourse practices (e.g., uses of speech and written genres for public presentation of candidates for knowledge, creation of peer-review texts, and standardization through textbook publishing) (Bazerman, 1988;Collins, 1985;Mukerji, 1989;Traweek, 1988). That is, across multiple disciplines studying scientific practices, there is a view that scientific knowledge is public, subject to debate, scrutiny, assessment, certification, or rejection by a relevant community (Duschl, 1990;Longino, 1990;Toulmin, 1982; for reviews see Kelly, 1997;Kelly & Chen, 1999;Kelly & Green, 1998). In a review of sociology of science from varying schools of thought, Zuckerman (1988) explained as follows, "Scientific knowledge is public, not private knowledge; contributions are not scientific until they are made public and subjected to evaluation by qualified experts" (p. 556).…”
Section: Introductionmentioning
confidence: 99%